2015
DOI: 10.1080/13548506.2015.1062523
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the feasibility and acceptability of health psychology-informed obesity training for medical students

Abstract: Health psychologists have succeeded in identifying theory-congruent behaviour change techniques (BCTs) to prevent and reduce lifestyle-related illnesses, such as cardiovascular disease, cancers and diabetes. Obesity management discussions between doctors and patients can be challenging and are often avoided. Despite a clear training need, it is unknown how best to tailor BCT research findings to inform obesity-management training for future healthcare professionals. The primary objective of this descriptive st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(45 citation statements)
references
References 32 publications
0
45
0
Order By: Relevance
“…By changing the way obesity is taught in the classroom to include the understanding of how stigma operates will, we hope, help stem the salience of such unacceptable practice in the future. Promising educational interventions include videos explaining stigma and its effects on individual lives (Swift et al, 2013b;Poustchi et al, 2013) and obesity training focusing on the behaviours related to obesity (Chisholm et al, 2016).…”
Section: The Implicit and Explicit Stigma Underpinning Obesity Managementioning
confidence: 99%
“…By changing the way obesity is taught in the classroom to include the understanding of how stigma operates will, we hope, help stem the salience of such unacceptable practice in the future. Promising educational interventions include videos explaining stigma and its effects on individual lives (Swift et al, 2013b;Poustchi et al, 2013) and obesity training focusing on the behaviours related to obesity (Chisholm et al, 2016).…”
Section: The Implicit and Explicit Stigma Underpinning Obesity Managementioning
confidence: 99%
“…Educating counselors about the role and importance of psychosocial constructs presents the ideal means for utilizing psychological research to benefit population health. Clinicians and medical students have been successfully trained to elicit and respond to patient statements indicating negative attitudes and norms toward engaging in health promoting behaviors (Chisholm et al, 2016; Fisher et al, 2004), providing a model for how genetic counselors might be similarly trained.…”
Section: Discussionmentioning
confidence: 99%
“…In their studies, Australian researchers have found that patients with type 2 diabetes are discriminated by society [12]. A. Chisholm et al [13] indicates the disease dependence on lifestyle and instructs how to prevent it. K. Park et al [14] study is devoted to the role of nutrition for people with diabetes.…”
Section: Discussionmentioning
confidence: 99%